KPM VERSUS PELNI: PERSAINGAN MEREBUT HEGEMONI JARINGAN PELAYARAN DI NUSANTARA, 1945–1960 - Bambang Surowo (Jurnal Sejarah Citra Lekha, 2016)
This study examines the competition between KPM versus PT Pelni in seizing the network hegemony cruise in the archipelago in 1945 to 1960 using the historical method. KPM is a major shipping company that was also founded by two major companies Rotterdamsche Lloyd (RL) and Stoomvaart Maatschappij Nederland (SMN) headquartered in Amsterdam the Netherlands. KPM serve scheduled regular shipping route for passengers and cargo between islands in the Dutch East Indies then more popular with the term as a post cruise between islands. KPM also play an important role to support and assist the colonial government in the process of penetration and pacification (conquest), especially in areas outside Java. On the other hand, PT PELNI established by the Indonesian government in the framework of the national development of a country that is still young, especially in the field of shipping. PELNI as well as KPM, also serves as centraal vervoersapparaat. Therefore, the government considers KPM c.q PELNI that dominate the cruise between islands in Indonesia are competitors and inhibitors of national development in the field of shipping. Post-transfer of sovereignity and the cancellation of the agreement KMB unilaterally by President Sukarno on May 3, 1956 resulted in the position of Dutch companies including KPM are at stake. This was exacerbated by the outbreak of the conflict between Indonesia and the Netherlands on Dutch New Guinea or West Papua, Indonesia implement the program so that the overall nationalization of the Dutch companies, including KPM.